2000
DOI: 10.1063/1.1150392
|View full text |Cite
|
Sign up to set email alerts
|

Some consequences to ion source behavior of high plasma drift velocity

Abstract: We consider the case of energetic ion beam formation when the ion streaming velocity within the source plasma is substantial, i.e., when the ions have a drift speed (in the positive downstream direction) that is on the order of or greater than the ion acoustic speed in the plasma. Some interesting consequences can follow, including the capability of a negatively biased substrate located in the plasma stream to maintain high bias voltage, and of an ion source with no extractor or “conventionally poor” extractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…17 Recently, it has been shown that magnetic field can affect the thickness of the near-substrate sheath. 18 The parameters of various systems without 19 and with 20 the transverse magnetic field have been investigated in the regime when the substrate bias pulses were applied at a rate of several hertz.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, it has been shown that magnetic field can affect the thickness of the near-substrate sheath. 18 The parameters of various systems without 19 and with 20 the transverse magnetic field have been investigated in the regime when the substrate bias pulses were applied at a rate of several hertz.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The processes that occur near the target surface ͑in the plasma sheath͒ during extraction of ion flow from the plasma are most important for surface treatment. Some effects were studied previously for systems without magnetic field 8,9 and in the presence of transverse magnetic field 10 for the case of voltage applied to the target in pulses with a frequency of several Hz. It was also shown recently that magnetic field can be used for control of the sheath expansion.…”
Section: Introductionmentioning
confidence: 99%